Environmental changes and geomorphic hazards in forests : report no. 4 of the IUFRO Task Force on Environmental Change - Sidle, Roy C. (IUFRO research series, 2002)
This book reviews current knowledge of most types of geohazards in forested areas. The 11 chapters cover hydrologic impacts, including flooding and soil erosion, desertification in Mediterranean Europe and Africa, landslides, and hazards in mangrove forests and along shorelines. Examples covered are from all five continents.